Contribution Analisis of Scientific Attitudes Towards Student Achievements Department of Physics Education in Universitas Papua - Rafy Iklashi; Mujasam Mujasam; Irfan Yusuf; Sri Wahyu Widyaningsih (Kasuari: Physics Education Journal (KPEJ), 2019)
Research has been conducted to determine the effect of scientific attitudes on student achievement in the Department of Physics Education at the University of Papua. This research is an associative descriptive research that describes the results of measurement of scientific attitudes and student achievement. The sample in this study were 21 students who filled out a scientific attitude questionnaire distributed via Google Form. Data collection techniques used are non-test techniques and documentation. Non-test technique in the form of giving a scientific attitude questionnaire to students. The questionnaire is filled in online through a Google form that is designed so that students can fill out whenever and wherever they are. The documentation technique is in the form of tracking student achievement indexes through Papua University's integrated sistem page. The results of the assessment of student responses were analyzed using Rusch modeling using the Winstep application. Spearman's rho analisis technique is used through the SPSS application to determine the effect of scientific attitudes on learning achievement. The measurement results of the influence of scientific attitudes on the Grade Point Average (GPA) obtained significance value of 0,539 is greater than the significance value of 0,05 which indicates that there is no significant effect between scientific attitudes on student GPA. The scientific attitude of students also obtained relatively low results. The low measurement results indicate that students of the Department of Education at the University of Papua need to be trained to develop their scientific attitude.